2015
DOI: 10.1007/s11356-015-5098-y
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance of Pseudomonas spp. isolated from wastewater and wastewater-impacted marine coastal zone

Abstract: In this study, species distribution and antimicrobial susceptibility of cultivated Pseudomonas spp. were studied in influent (INF), effluent (EFF), and marine outfall (MOut) of wastewater treatment plant (WWTP). The susceptibility was tested against 8 antimicrobial classes, active against Pseudomonas spp.: aminoglycosides, carbapenems, broad-spectrum cephalosporins from the 3rd and 4th generation, extended-spectrum penicillins, as well as their combination with the β-lactamase inhibitors, monobactams, fluoroqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 45 publications
3
29
0
1
Order By: Relevance
“…21 ESBL-producing isolates were recovered from the five river effluents (n = 12) and Al-Qaa refugee camp (n = 9). The ESBL-producing E. coli detected were additionally MDR, which was in harmony with Luczkiewicz et al, findings that also reported on MDR ESBLs in treated wastewater treatment plant [20]. On the other hand, resistance to penicillins (amoxicillin, tricarcillin and piperacillin), penicillin/inhibitor combination (amoxicillin-calvulanate [AMC] and piperacillin-tazobacatam), quinolones and cephalosporins was very common among the ESBLs undertaken in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…21 ESBL-producing isolates were recovered from the five river effluents (n = 12) and Al-Qaa refugee camp (n = 9). The ESBL-producing E. coli detected were additionally MDR, which was in harmony with Luczkiewicz et al, findings that also reported on MDR ESBLs in treated wastewater treatment plant [20]. On the other hand, resistance to penicillins (amoxicillin, tricarcillin and piperacillin), penicillin/inhibitor combination (amoxicillin-calvulanate [AMC] and piperacillin-tazobacatam), quinolones and cephalosporins was very common among the ESBLs undertaken in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Despite their diversity, some characters are shared between different strains when exposed to similar environments, which is attributed to selection pressure [19]. Previous studies on the resistance patterns of E. coli isolated from sewage showed the highest resistance to tetracycline, ampicillin/clavulanic acid and trimethoprim/sulfamethoxazole [20][21]. Additionally, CTX-M-15 and TEM were among the most common resistance determinants detected in ESBL-producing E. coli recovered from water networks [22].…”
mentioning
confidence: 99%
“…In addition, the result of the resistance pattern of the Pseudomonas sp. to colistin sulphate and piperacillin were similar to a previous report on wastewater and wastewater impacted marine coastal zone where the Pseudomonas isolates from the study were completely susceptible to colistin sulphate and only one of the 146 isolates was resistant to piperacillin [24]. In a study carried out on clinical isolates in Jamaica, the reported Pseudomonas species resistance was 17.6% (piperacillin), 19.6% (ceftazidime) and 9.8% (imipenem and meropenem) [25].…”
Section: Discussionsupporting
confidence: 87%
“…Surprisingly, 4 out of 11 evaluated strains exhibited co-resistance to more than three antimicrobial agents and were defined as MDR strains. These results were similar to those obtained by Luczkiewicz, Kotlarska, Artichowicz, Tarasewicz and Fudala-Ksiazek (2015). The natural resistance of P. aeruginosa to different antibiotics is mainly attributed to the presence of the mexA and mexB genes among evaluated isolates, which in turn reduce the permeability of the bacterial cell wall to antibiotics (Li, Nikaido & Poole, 1995).…”
Section: Discussionsupporting
confidence: 88%